The primacy of Law over Ethics? A New Phase of the Italian Dispute over in vitro Method - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2015)
In April 2014 The Constitutional Court in Italy was called to judge parts of the Law 40/2004 and canceled the prohibition of the methods of heterological artificial reproduction. !is decision opened a new stage of the public dispute about artificial reproduction that has been held in Italy for the last 20 years. The most significant principle of the legislation from the year 2004 was the recognition of the human embryo as a human being from the very moment of conception. The law in Italy forbade, among others, producing human embryos for scientific purposes, freezing and destroying human beings. The opponents of such legal regulations evoked the nationwide referendum in 2005 which did not manage to repeal the operative legislation. In 2015 the Italian Parliament will adopt a special law regulating the use of the methods of heterological artificial reproduction.